2015
DOI: 10.18488/journal.89/2015.1.1/89.1.8.26
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Dividend Policy on Shareholders’ Wealth before and After Financial Melt down: Evidence from FMCG Sector in India

Abstract: Dividend policy (DP) of corporate sector is widely researched topic in finance however; it remains a debatable issue to decide what factors determine the DP. The objective of this paper is to analyze the impact of dividend policy (DP) on shareholders' wealth (SW) of Fast Moving Consumer Goods (FMCG) sector in India. Out of 16 firms listed on National Stock Exchange (NSE) 13 firms that have been paying dividend consecutively for the past ten years are considered for analysis. In the light of the prior literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 3 publications
4
4
0
2
Order By: Relevance
“…This study fail to reject the research hypotheses that dividend per share affect shareholders' wealth (earnings per share) of listed manufacturing companies in Nigeria. This findings is in line with the studies of Travlos and Trigeorgis Vafeas ( 2001), Azhagaiah and Sabari Priya (2008), Hassan, Asaduzzaman and Karim (2013), Sarwar (2013), Alim, Ali, Ali, Khattak and Qureshi (2014), Mathew, Innocent and Mike (2014), Sarwar and Naseem (2014 and Gejalakshmi Azhagaiah (2015) and Iram (2015) found positive effect of dividend per share on market price per share. However, Hussain (2010) who found negative effect of dividend per share on market price per share.…”
Section: Dividend Per Share and Shareholders' Wealth (Market Price Per Share)supporting
confidence: 87%
See 1 more Smart Citation
“…This study fail to reject the research hypotheses that dividend per share affect shareholders' wealth (earnings per share) of listed manufacturing companies in Nigeria. This findings is in line with the studies of Travlos and Trigeorgis Vafeas ( 2001), Azhagaiah and Sabari Priya (2008), Hassan, Asaduzzaman and Karim (2013), Sarwar (2013), Alim, Ali, Ali, Khattak and Qureshi (2014), Mathew, Innocent and Mike (2014), Sarwar and Naseem (2014 and Gejalakshmi Azhagaiah (2015) and Iram (2015) found positive effect of dividend per share on market price per share. However, Hussain (2010) who found negative effect of dividend per share on market price per share.…”
Section: Dividend Per Share and Shareholders' Wealth (Market Price Per Share)supporting
confidence: 87%
“…This findings is in line with the studies of Ponsian, Prosper, Yuda & Samwel (2015) who found negative effect of dividend yield on market price per share. However, Wet and Mpinda (2013), Al-Masum (2014), Bilal andJamil (2015) and Gejalakshmi and Azhagaiah (2015) found positive effect of dividend yield on market price per share.…”
Section: Dividend Yield and Shareholders' Wealth (Market Price Per Share)mentioning
confidence: 97%
“…Jika perusahaan berkembang pesat, maka laba dan dividen juga akan meningkat, sehingga nilai perusahaan akan meningkat. Menurut Azhagaiah dan Gejalakshmi (2015) harga pasar saham adalah nilai pasar perusahaan yang dapat diperoleh investor apabila investor menjual atau membeli saham, yang ditentukan berdasarkan harga penutupan di bursa.…”
Section: Kekayaan Pemegang Sahamunclassified
“…Retained earnings menurut Azhagaiah dan Gejalakshmi (2015) adalah sebagian atau seluruh laba yang diperoleh perusahaan yang tidak dibagikan kepada pemegang saham sebagai dividen. Sedangkan menurut Brigham dan Houston (2010) retained earnings adalah laba yang tersedia bagi para pemegang saham biasa yang ditahan oleh perusahaan untuk diinvestasikan kembali atau reinvestment yang tujuannya untuk meningkatkan pertumbuhan perusahaan.…”
Section: Retained Earning Per Sharesunclassified
“…The argument for dividend policy relevance theory was supported by Walter (1963), who argues that investors prefer to receive the dividends now so that they can reinvest and earn a further return in the future. Further studies which supported this argument are (Gejalakshmi and Azhagaiah, 2015;Ali et al, 2015). The dividend policy irrelevance theories are based on the ground that the dividend policy of the firm is independent of the market share price and thus the dividend policy decision is a passive residual.…”
Section: Theoretical Literaturementioning
confidence: 96%